Analisis Kesulitan Belajar Mahasiswa dalam Menyelesaikan Masalah Matematika ke-MI/SD-an Program Studi Pendidikan Guru Madrasah Ibtidaiyah - Rustam, Faisya Rahayu; Danial, Danial; Syarifuddin, Syarifuddin; Fitriani, Fitriani (JTMT: Journal Tadris Matematika, 2022)
This study aims to describe students' learning difficulties in solving math problems for MI/SD based on Polya's problem-solving stages. This research is included in the case study research using a qualitative approach. The subjects of this study were 2 students of the PGMI study program who had studied Mathematics for MI/SD. The data collection methods in this study were tests and interviews, while the data analysis was done by reducing data, presenting data, and drawing conclusions. The results showed that the learning difficulties experienced by RSD and SAT were broadly similar, including: (1) difficulty in understanding the problem, such as being unable to understand the problem from the question, unable to determine the appropriate symbol with the information known from the question, incomplete in writing down the information contained in the questions, and still lacking in understanding the concept; (2) difficulty in planning problem solving, such as being unable to determine symbols and mathematical concepts or formulas; (3) difficulty in implementing the problem-solving plan, such as not sure about the concept or formula used, and difficulty in doing the exercises without looking at the example; (4) difficulty in re-examining the solution obtained, namely not knowing how to re-examine correctly.